Analisis Perubahan Anggaran Sebelum Dan Saat Pandemi COVID-19 di Kota Subulussalam - Virta Sari; Afrah Junita; Muhammad Salman (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to determine budget changes before and during the COVID-19 pandemic in Subulussalam City. This study uses quantitative methods descriptip. Sources of data from this study are changes in the regional budget (P-APBD) and Budget realization report (LRA) obtained from the regional apparatus organization (OPD). which consists of the years 2018-2021. Data analysis method using paired Sample t-Test difference test known Sig value. (2-tailed) is 0.009 which is less than 0.05, then Ho is rejected and Ha is accepted with: Ha = there is a difference between budget changes before the pandemic and during the COVID-19 pandemic. so it can be concluded that there is a significant budget change between the budget changes before and during the COVID-19 pandemic due to an increase in changes to the regional budget in 2020 and 2021 for efforts to increase handling of the COVID-19 pandemic in Subulussalam City.